2022
DOI: 10.1002/smtd.202201070
|View full text |Cite
|
Sign up to set email alerts
|

Strain Gradient Programming in 3D Fibrous Hydrogels to Direct Graded Cell Alignment

Abstract: Biological tissues experience various stretch gradients which act as mechanical signaling from the extracellular environment to cells. These mechanical stimuli are sensed by cells, triggering essential signaling cascades regulating cell migration, differentiation, and tissue remodeling. In most previous studies, a simple, uniform stretch to 2D elastic substrates has been applied to analyze the response of living cells. However, induction of nonuniform strains in controlled gradients, particularly in biomimetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The silicone carrier can also aid with in-vivo implantation of the gel in desired tissue region, for regenerative medicine applications. The silicone carrier can also be exploited in biomechanical stretching experiments, in which the gel can be strained externally through stretch of the silicone carrier, as we demonstrated in our previous studies [59][60][61]. The silicone carrier also facilitates the stacking of several layers of patterned gels to create a 3D layered assembly of gel-patterned cells, as we have demonstrated.…”
Section: Discussionmentioning
confidence: 81%
“…The silicone carrier can also aid with in-vivo implantation of the gel in desired tissue region, for regenerative medicine applications. The silicone carrier can also be exploited in biomechanical stretching experiments, in which the gel can be strained externally through stretch of the silicone carrier, as we demonstrated in our previous studies [59][60][61]. The silicone carrier also facilitates the stacking of several layers of patterned gels to create a 3D layered assembly of gel-patterned cells, as we have demonstrated.…”
Section: Discussionmentioning
confidence: 81%
“…1,2 The mechanical signals continuously stimulate cells and trigger different behaviors regulating cell activities, such as growth, proliferation, and migration. [3][4][5] Studies have demonstrated that mechanical stimulation affects organ morphogenesis, 6 skeletal muscle differentiation, 7 and central nervous system development. 8 However, it is difficult to directly observe the mechanisms of cell mechanobiological responses due to the complexity of the in vivo environment, and the challenges also occur in studying cell responses in isolated animal tissues.…”
Section: Introductionmentioning
confidence: 99%